Pembangunan Jaringan Transportasi di Lampung (1859 -1927) - Gregorius Andika Ariwibowo; Hary Ganjar Budiman; Dana Listiana (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2023)
The development of transportation networks has been an important factor in accelerating economic and trade progress in Lampung and southern Sumatra since the second decade of the 20th century. The development of transportation facilities has changed the centers of economic activity and settlements in the Lampung region from being centered around rivers to roads and railways. This article discusses the development of transport networks to support the changes in the Lampung region from the mid-19th century to the third decade of the 20th century. This study also explains the development of transport facilities in creating trans Java-Sumatra economic integration during the colonial period. This study aimed to reconstruct the financial history and transport networks of the Lampung region. This study provides a perspective on forming the trans-Sumatra transport network that made Lampung known as the "Gateway of Sumatra.” The study on "The Development of Transportation Network in Lampung (1859-1927)" was prepared using a historical method that included four stages of work: heuristics, verification, interpretation, and historiography. The development of integrated transport facilities in the Lampung region since the end of the war in 1856 has changed various aspects of the lives of the Lampung people. This study showed that the river has no longer become an essential part of the life of the Lampung people since the mid-19th century. Settlement patterns and economic activity centers located on the riverside began to change following the road and railway lines that were formed later. Keywords: transportation network; Lampung; Zuid-Sumatra spoorwagen; Dutch East Indies transportation system; modernization of the Dutch East Indies